Carbon-coated current collector and preparation method thereof
By using modified conductive carbon slurry to form a modified carbon layer on the surface of the aluminum foil, the problem of insufficient compatibility between the aluminum foil and the positive electrode material is solved, and higher adhesion and hydrophobic performance are achieved, extending the service life of the battery and improving the overall performance.
Patent Information
- Application Number
- CN202510035841.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-05-09
AI Technical Summary
In the prior art, the physical and chemical compatibility between the aluminum foil and the positive electrode material is insufficient, resulting in low polarity of the conductive carbon layer, affecting the adhesion and interface resistance of the positive electrode material, and there are challenges in the dosage ratio of the silane coupling agent, the adhesion and hydrophobicity of the modified carbon layer, the uniformity and stability.
Modified conductive carbon slurry, including binder, silane coupling agent and conductive material, are mixed at a specific ratio to form a modified carbon layer. Through the double-sided coating and drying process, a coating current collector is formed to enhance the adhesion and hydrophobic properties of the modified carbon layer on the surface of the aluminum foil.
It improves the bonding force between the positive electrode coating and the current collector, reduces the bulge caused by moisture in the battery, extends the service life of the battery, and improves the overall performance of the battery.
Smart Images

Figure BDA0005235518880000061 
Figure BDA0005235518880000071
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of battery separators, and in particular relates to a carbon-coated current collector and a preparation method thereof. Background Art
[0002] As one of the key technologies in the field of new energy, the continuous optimization of the performance of lithium-ion batteries is crucial to promoting the development of electric vehicles, energy storage systems and portable electronic devices. In the battery structure, the performance of the positive electrode current collector is directly related to the energy density, cycle stability and battery safety of the battery. The interface interaction between aluminum foil and the positive electrode material has always been one of the key factors limiting the improvement of battery performance. In order to solve the physical and chemical compatibility problems between aluminum foil and the positive electrode material, a conductive carbon layer is coated between the aluminum foil and the positive electrode coating to improve the compatibility between the two and improve the overall performance of the battery. The unmodified conductive carbon layer usually has a lower polarity, which affects the adhesion and interface resistance of the positive electrode material on the aluminum foil.
[0003] As a dual-reactive compound, silane coupling agent can form a chemical bond with inorganic materials (such as metal hydroxyl Me-OH on the surface of aluminum foil) at one end, and react with organic polymers (such as binders) at the other end, thus building a bridge between the inorganic and organic interfaces and effectively improving the compatibility of materials. Although some progress has been made in existing research, there are still many challenges in the existing technology, such as the dosage ratio of silane coupling agent, the adhesion and hydrophobicity of the modified carbon layer (conductive carbon layer), and ensuring the uniformity and stability of the modified carbon layer. Summary of the invention
[0004] In view of the deficiencies of the prior art, an object of the present invention is to provide a carbon-coated current collector.
[0005] Another object of the present invention is to provide a method for preparing the above-mentioned carbon-coated current collector.
[0006] Another object of the present invention is to provide a modified conductive carbon slurry.
[0007] Another object of the present invention is to provide a battery.
[0008] The purpose of the present invention is achieved through the following technical solutions.
[0009] A carbon-coated current collector, which is a carbon-coated aluminum foil, comprises: an aluminum foil and a modified carbon layer on the aluminum foil, the modified carbon layer comprises: a binder, a silane coupling agent and a conductive material, and the ratio of the binder, the silane coupling agent and the conductive material is (15-20): (1-3): (4.5-5) by mass.
[0010] In the above technical solution, the ratio of the binder, the silane coupling agent and the conductive material is preferably (18-18.5): (2.5-3): (4.5-4.8) in parts by mass.
[0011] In the above technical solution, the binder is a polyacrylic acid adhesive (colorless to light yellow liquid), the solid content of polyacrylic acid in the polyacrylic acid adhesive is 20-25wt%, the viscosity of the polyacrylic acid adhesive is 1200-1400mPa·s, and the pH of the polyacrylic acid adhesive is 2-3.
[0012] In the above technical solution, the silane coupling agent is (3-glycidylpropoxy)trimethoxysilane (clear and transparent appearance).
[0013] In the above technical solution, the conductive material is one or a mixture of several of acetylene black, Ketjen black, Super P-Li carbon black, conductive graphite, graphene and carbon nanotubes.
[0014] The preparation method of the above-mentioned carbon-coated current collector includes: coating the modified conductive carbon slurry on both sides of the aluminum foil surface, drying, obtaining modified carbon layers on both sides of the aluminum foil, and obtaining the carbon-coated current collector. The modified conductive carbon slurry includes: a binder, a solvent, a silane coupling agent and a conductive material.
[0015] In the above technical solution, the thickness of the modified carbon layer on each side is 0.5-0.8 μm.
[0016] In the above technical solution, the drying time is 1 to 3 minutes, and the drying temperature is 50 to 70°C.
[0017] In the above technical solution, the coating speed is 30 to 50 m / min.
[0018] In the above technical solution, the solvent is water.
[0019] A modified conductive carbon slurry comprises: a binder, a solvent, a silane coupling agent and a conductive material. The ratio of the binder, the solvent, the silane coupling agent and the conductive material is (15-20): (73-80): (1-3): (4.5-5) by mass.
[0020] In the above technical solution, the ratio of the binder, the solvent, the silane coupling agent and the conductive material is preferably (18-18.5): (73-75): (2.5-3): (4.5-4.8) by mass.
[0021] The method for preparing the modified conductive carbon slurry comprises: mixing a binder, a solvent, a conductive material and a silane coupling agent until they are uniform, so as to obtain the modified conductive carbon slurry.
[0022] The method for preparing the above-mentioned modified conductive carbon slurry specifically includes: mixing the binder and the solvent until uniformly to obtain a (transparent and particle-free) first glue solution, mixing the first glue solution and the conductive material until uniformly to obtain a conductive carbon slurry, and mixing the conductive carbon slurry and the silane coupling agent until uniformly to obtain a modified conductive carbon slurry.
[0023] In the above technical solution, the binder and the solvent are mixed and stirred at a rotation speed of 1300 to 1800 r / min and a revolution speed of 30 to 50 r / min for 2 to 3 hours until they are uniform, thereby obtaining the first adhesive solution.
[0024] In the above technical solution, the first glue liquid and the conductive material are mixed, first stirred at a rotation speed of 1800-2200r / min and a revolution speed of 30-50r / min for 50-80min, and then sand-milled at a speed of 500-600rpm for 10-25min until uniform, to obtain the conductive carbon slurry.
[0025] In the above technical solution, the conductive carbon slurry and the silane coupling agent are mixed, and stirred at a rotation speed of 1800 to 2200 r / min and a revolution speed of 30 to 50 r / min for 30 to 40 minutes until uniform, to obtain the modified conductive carbon slurry.
[0026] A battery comprises: a positive electrode plate, wherein the current collector used by the positive electrode plate is the carbon-coated aluminum foil.
[0027] In the above technical solution, the positive electrode plate includes the carbon-coated aluminum foil and the positive electrode coating.
[0028] In the above technical solution, the positive electrode coating includes: PVDF, lithium iron phosphate and a conductive agent. In terms of mass fractions, the ratio of PVDF, lithium iron phosphate and the conductive agent is (1-1.5): (40-43): (0.5-1).
[0029] In the above technical scheme, the positive electrode coating is formed by coating the positive electrode slurry. The method for preparing the positive electrode slurry includes: mixing PVDF and NMP until uniform to obtain a transparent positive electrode slurry without colloid particles, mixing the positive electrode slurry and lithium iron phosphate (powder) until uniform, then adding a conductive agent, mixing until uniform, standing and degassing to obtain a positive electrode slurry. The ratio of PVDF, NMP, lithium iron phosphate and conductive agent is (1-1.5): (50-57): (40-43): (0.5-1) by mass.
[0030] In the method for preparing the positive electrode slurry, PVDF and NMP are mixed, and stirred at a speed of 1000 to 1200 r / min for 1 to 2 hours until they are uniform, thereby obtaining the positive electrode glue solution.
[0031] In the method for preparing positive electrode slurry, the positive electrode glue and lithium iron phosphate (powder) are mixed, stirred at a speed of 800 to 1000 r / min for 1 to 2 hours until uniform, and then a conductive agent is added, stirred at a speed of 800 to 1000 r / min for 1 to 2 hours until uniform, and allowed to stand for degassing to obtain positive electrode slurry.
[0032] In the method for preparing positive electrode slurry, the conductive agent is one or a mixture of several of acetylene black, Ketjen black, Super P-Li carbon black, conductive graphite, graphene and carbon nanotubes.
[0033] Application of silane coupling agent in improving the adhesion between electrode coating and current collector.
[0034] Application of silane coupling agent in improving battery capacity retention rate.
[0035] (3-Glycidylpropoxy)trimethoxysilane and polyacrylic acid adhesive work synergistically to enhance the bonding strength between the coating and the aluminum foil.
[0036] Compared with the prior art, the present invention has the following beneficial effects:
[0037] The invention introduces a specific silane coupling agent for modification, thereby improving the adhesion of the modified carbon layer on the surface of the aluminum foil, and having good hydrophobic properties, reducing the bulging phenomenon of the battery caused by moisture. At the same time, the adhesion between the positive electrode coating and the current collector is improved, thereby reducing the powdering and delamination phenomenon of the positive electrode coating, reducing the attenuation of the battery capacity, and extending the service life of the battery. DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0039] (3-Glycidyl propoxy) trimethoxy silane has a special molecular structure, with different groups at both ends, one end is a silane group with three methoxy groups, and the other end is a glycidyl propoxy functional group with an epoxy ring. After dehydration and condensation, the methoxy group combines with the inorganic material (aluminum foil) to form a strong metal bond. Among the usually 0 to 3 hydrolyzable groups, (3-glycidyl propoxy) trimethoxy silane has 3 hydrolyzable groups, forming a tight 3D matrix with the substrate (aluminum foil); and the glycidyl propoxy functional group is more compatible with polyacrylic acid adhesives, which enhances the bonding force between the coating and the substrate (aluminum foil), making the coating adhesion better and reducing the shedding of the coating during the battery charge and discharge cycle; and the glycerol group is hydrophobic, and these groups tend to gather together, reducing direct contact with water molecules and improving hydrophobicity.
[0040] Double planetary mixer (planetary mixing equipment) - Hongshang Machinery HY-DLH43L; Sand grinder - Langling Machinery NT-V2L.
[0041] Examples 1 to 3
[0042] A method for preparing a modified conductive carbon slurry comprises: mixing a binder and a solvent, stirring the mixture in a planetary stirring device at a rotation speed of 1500 r / min and a revolution speed of 40 r / min for 2.5 hours until the mixture is uniform, obtaining a transparent first glue solution without glue particles, mixing the first glue solution and a conductive material (the conductive material is slowly added to the first glue solution in 5 times to prevent accumulation), stirring the mixture in a planetary stirring device at a rotation speed of 2000 r / min and a revolution speed of 40 r / min for 70 minutes, and then sand-milling the mixture in a sand mill at a speed of 550 rpm for 20 minutes until the mixture is uniform, obtaining a conductive carbon slurry, and mixing the conductive carbon slurry with a silane coupling agent. The mixture was mixed and stirred in a planetary stirring device at a rotation speed of 2000 r / min and a revolution speed of 40 r / min for 35 min until uniform, to obtain a modified conductive carbon slurry, wherein the ratio of the binder, the solvent, the silane coupling agent and the conductive material is X by weight, the binder is a polyacrylic acid adhesive (a colorless to light yellow liquid, the solid content of polyacrylic acid in the polyacrylic acid adhesive is 24.4wt%, the viscosity of the polyacrylic acid adhesive is 1394 mPa·s, and the pH of the polyacrylic acid adhesive is 2.5), the solvent is water, the silane coupling agent is (3-glycidyl propoxy) trimethoxy silane (clear and transparent appearance), and the conductive material is Super P-Li carbon black. The value of X is shown in Table 1.
[0043] Table 1
[0044] Modified conductive carbon slurry X Example 1 19:75:1:5 Example 2 18.7:74.6:2:4.7 Example 3 18.4:74:3:4.6
[0045] Comparative Example 1
[0046] A method for preparing a conductive carbon slurry comprises: mixing a binder and a solvent, stirring the mixture in a planetary stirring device at a rotation speed of 1500 r / min and a revolution speed of 40 r / min for 2.5 h until the mixture is uniform, to obtain a transparent first colloid-free colloid solution, mixing the first colloid solution and a conductive material (the conductive material is slowly added to the first colloid solution in 5 times to prevent accumulation), stirring the mixture in a planetary stirring device at a rotation speed of 2000 r / min and a revolution speed of 40 r / min for 70 min, and then sand-milling the mixture in a sand mill at a speed of 550 rpm for 20 min until the mixture is uniform, to obtain a conductive carbon slurry, wherein the ratio of the binder, the solvent and the conductive material is 19:76.2:4.8 by mass, the binder is the same as that in Example 1, the solvent is water, and the conductive material is Super P-Li carbon black.
[0047] Comparative Example 2
[0048] A method for preparing a modified conductive carbon slurry is basically the same as that of Example 3, except that "(3-glycidylpropoxy)trimethoxysilane" in Example 3 is replaced by "vinyltriethoxysilane".
[0049] Comparative Example 3
[0050] A method for preparing a modified conductive carbon slurry is basically the same as that of Example 3, except that "(3-glycidylpropoxy)trimethoxysilane" in Example 3 is replaced by "γ-(2,3-epoxypropoxy)propyltrimethoxysilane".
[0051] Examples 4 to 6 and Comparative Examples 4 to 6
[0052] A battery, comprising: a positive electrode sheet, a negative electrode sheet and an electrolyte, wherein the negative electrode material in the negative electrode sheet is graphite, the electrolyte is a mixture of an electrolyte and a solvent, and the electrolyte is LiPF 6 The concentration of the electrolyte in the electrolyte is 1 mol / L, the solvent is a mixture of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate, and the volume ratio of ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate is 1:1:1. The method for preparing the positive electrode plate comprises: placing a 90 mm*1200 mm current collector (the current collector is a carbon-coated aluminum foil) on a positive electrode scraping coating device, coating the positive electrode slurry on both sides of the current collector surface, drying in an oven at 70°C for 4 hours, and obtaining positive electrode coatings with single-sided thicknesses of 200 μm and 200 μm on both sides of the current collector, respectively, to obtain a positive electrode plate, wherein the method for obtaining the current collector is: coating the conductive carbon slurry on both sides (the coating speed is 40 m / min) on the surface of the aluminum foil, drying at 60°C for 2 minutes, and obtaining carbon layers with single-sided thicknesses of 0.8 μm and 0.8 μm on both sides of the aluminum foil, respectively, to obtain a current collector. The conductive carbon slurry is one of the modified conductive carbon slurries prepared in Examples 1 to 3 and Comparative Examples 2 to 3 and the conductive carbon slurry prepared in Comparative Example 1 (the carbon layer obtained in Examples 1 to 3 and Comparative Examples 2 to 3 is a modified carbon layer).
[0053] The method for preparing positive electrode slurry includes: mixing PVDF and NMP, stirring at a speed of 1100r / min for 1.5 hours until uniform, to obtain a transparent positive electrode slurry without colloid particles, mixing the positive electrode slurry and lithium iron phosphate (powder), stirring at a speed of 900r / min for 1 hour until uniform, then adding a conductive agent, stirring at a speed of 900r / min for 1 hour until uniform, standing for 2 hours for degassing, and obtaining a positive electrode slurry. The ratio of PVDF, NMP, lithium iron phosphate and conductive agent is 1.3:55:42:0.7 by mass, and the conductive agent is Super P-Li carbon black.
[0054] The current collector and the positive electrode sheet obtained from the conductive carbon slurries obtained in the above Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the test results are shown in Table 2.
[0055] Table 2
[0056]
[0057] Silane primer adhesion: Cut the current collector (carbon-coated aluminum foil) into strips of 100mm*25mm, use 3M transparent tape to stick to the surface of the current collector (carbon-coated aluminum foil), roll it unidirectionally with a 2kg roller for 4 times, fix it on an electronic tensile testing machine, peel off the 3M transparent tape at a speed of 100mm / min, and the average value of the force value is the silane primer adhesion.
[0058] Positive electrode peeling force: Cut the positive electrode sheet into 50mm*20mm strips, use 3M double-sided tape to stick the positive electrode sheet to the steel plate, roll it back and forth 8 times with a 2kg roller, fix it on the electronic tensile testing machine with the steel plate at the bottom and the positive electrode sheet at the top, pull the steel plate and the positive electrode sheet apart at a speed of 50mm / min, and get the average force value. The average force value / tested length of the positive electrode sheet (25mm) is used to get the positive electrode peeling force (N / m). The positive electrode peeling force is used to characterize the bonding force between the positive electrode coating and the current collector (carbon-coated aluminum foil).
[0059] Impedance: Place the current collector (carbon-coated aluminum foil) in a pneumatic pressurization device (test area: 78.5mm 2 , force value: 4MPa) between the positive and negative poles, connect the internal resistance tester to perform impedance test.
[0060] Hydrophobic wiping: Use a cotton swab soaked in water to wipe back and forth on the current collector (carbon-coated aluminum foil), and record the number of wipes when the carbon layer starts to fall off.
[0061] It can be concluded from the data in Table 2 that the current collectors of Examples 1 to 3 are carbon-coated aluminum foils prepared from modified conductive carbon slurries, and their silane primer adhesion is significantly improved compared with Comparative Examples 1 to 3; the number of hydrophobic wiping times of Examples 1 to 3 is significantly more than that of the Comparative Example, and the hydrophobic performance is improved compared with the Comparative Example; the positive electrode peeling force of Examples 1 to 3 is significantly improved compared with the Comparative Example, from 20 to 30 N / m to 40 to 60 N / m.
[0062] The batteries obtained from the conductive carbon slurries obtained in the above Examples 1 to 3 and Comparative Examples 1 to 3 were tested, and the test results are shown in Table 3.
[0063] Table 3
[0064]
[0065] As can be seen from Tables 2 and 3, the present invention greatly improves the bonding force between the positive electrode coating and the current collector and the hydrophobicity of the current collector without affecting other properties. After coating with the modified conductive carbon slurry modified with (3-glycidyl propoxy) trimethoxysilane, the various properties of Examples 4 to 6 are better than those of the unmodified battery and other batteries modified with silane coupling agents, thereby achieving the effect of improving the bonding force and the hydrophobicity of the current collector by using (3-glycidyl propoxy) trimethoxysilane for surface modification.
[0066] The present invention is described above by way of example. It should be noted that, without departing from the core of the present invention, any simple deformation, modification or other equivalent replacement that can be made by those skilled in the art without inventive effort falls within the protection scope of the present invention.
Claims
1. A carbon-coated current collector, characterized in that: The carbon-coated current collector is a carbon-coated aluminum foil, including: an aluminum foil and a modified carbon layer on the aluminum foil, the modified carbon layer includes: a binder, a silane coupling agent and a conductive material, and the ratio of the binder, the silane coupling agent and the conductive material is (15-20): (1-3): (4.5-5) by mass, and the silane coupling agent is (3-glycidylpropoxy)trimethoxysilane.
2. The carbon-coated current collector according to claim 1, characterized in that: The adhesive is a polyacrylic acid adhesive, and the viscosity of the polyacrylic acid adhesive is 1200-1400 mPa·s.
3. The carbon-coated current collector according to claim 1, characterized in that: The conductive material is one or a mixture of acetylene black, Ketjen black, Super P-Li carbon black, conductive graphite, graphene and carbon nanotubes.
4. The carbon-coated current collector according to claim 1, characterized in that: The solid content of polyacrylic acid in the polyacrylic acid adhesive is 20-25wt%, and the pH of the polyacrylic acid adhesive is 2-3.
5. The method for preparing a carbon-coated current collector according to any one of claims 1 to 4, characterized in that: include: The modified conductive carbon slurry is coated on both sides of the aluminum foil and dried to obtain modified carbon layers on both sides of the aluminum foil to obtain a carbon-coated current collector. The modified conductive carbon slurry includes: a binder, a solvent, a silane coupling agent and a conductive material.
6. A modified conductive carbon slurry, characterized in that: include: The binder, the solvent, the silane coupling agent and the conductive material are present in a ratio of (15-20): (73-80): (1-3): (4.5-5) by mass.
7. The method for preparing the modified conductive carbon slurry according to claim 6, characterized in that: include: The binder, solvent, conductive material and silane coupling agent are mixed until uniform to obtain modified conductive carbon slurry.
8. A battery comprising: A positive electrode plate, characterized in that the current collector used in the positive electrode plate is the carbon-coated aluminum foil as described in claim 1.
9. The use of a silane coupling agent in improving the bonding strength between an electrode coating and a current collector, characterized in that: The silane coupling agent is (3-glycidylpropoxy)trimethoxysilane.
10. The use of a silane coupling agent in improving battery capacity retention, characterized in that: The silane coupling agent is (3-glycidylpropoxy)trimethoxysilane.
Citation Information
Cited By
High-adaptability conductive paste, preparation method thereof and application of high-adaptability conductive paste in carbon-coated current collector
CN120600376A
Carbon-coated slurry, carbon-coated copper foil, negative plate and lithium ion battery
CN120718536A
Carbon-coated slurry, carbon-coated copper foil, negative electrode sheet and lithium-ion battery
CN120718536B
Aqueous zinc ion flexible soft package battery and preparation method thereof
CN121307248A
Oil-based conductive paste as well as preparation method and application thereof
CN122314914A